The impact of the flipped classroom strategy on the academic achievement and achievement motivation of mathematics course students and methods of teaching it under the Corona pandemic (Journal of the College of Basic Education, 2022)
The aim of the research is to study the special effects of the flipped classroom strategy on academic achievement and achievement motivation in light of the Corona pandemic. The research sample consisted of two groups: the experimental group, which numbered (34) students, and the control group, which numbered (35) students. Where the experimental group was taught using the flipped classroom strategy, while the control group was taught using the traditional method based on lectures, We used An achievement test in the mathematics and its teaching methods course and a measure of achievement motivation, The results showed that there was a statistically significant difference in academic achievement between the two groups For the benefit of the experimental group, There is a significant impact of the flipped classroom strategy on achievement, The results also showed that there was a statistically significant difference in achievement motivation between the two groups, For the benefit of the experimental group, And there is a significant impact of the flipped classroom strategy on achievement motivation, The research concluded that the flipped classroom strategy can be used if it is properly harnessed.